2007
DOI: 10.1098/rspb.2006.0394
|View full text |Cite
|
Sign up to set email alerts
|

Post-mating disparity between potential and realized immune response inDrosophila melanogaster

Abstract: Reproductive costs are an essential component of evolutionary theory. For instance, an increase in reproduction is generally coupled with a decrease in immunocompetence shortly after mating. However, recent work in Drosophila melanogaster suggests that the potential to mount an immune response, as measured by the levels of immune gene expression, increases after mating. These data are in contrast to previous studies, which suggest that mating can reduce a fly's ability to survive an actual bacterial challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 49 publications
9
96
3
Order By: Relevance
“…Other studies have measured overall defence as a function of mating in the context of experimental infection (McKean & Nunney 2001Shoemaker et al 2006;Fedorka et al 2007;Wigby et al 2008). Three of the cited studies have been performed using female D. melanogaster (McKean & Nunney 2005;Fedorka et al 2007;Wigby et al 2008), but no clear consensus has emerged even from those as to whether females suffer a meaningful reduction in immune defence after mating. Two of these studies (McKean & Nunney 2005;Wigby et al 2008) show no change owing to mating in the ability of females to clear non-pathogenic bacteria, while Fedorka et al (2007) demonstrated that females infected with a pathogenic bacterium suffer higher mortality if they have mated.…”
Section: Results and Discussion (A) Mating Reduces Female Immune Defementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have measured overall defence as a function of mating in the context of experimental infection (McKean & Nunney 2001Shoemaker et al 2006;Fedorka et al 2007;Wigby et al 2008). Three of the cited studies have been performed using female D. melanogaster (McKean & Nunney 2005;Fedorka et al 2007;Wigby et al 2008), but no clear consensus has emerged even from those as to whether females suffer a meaningful reduction in immune defence after mating. Two of these studies (McKean & Nunney 2005;Wigby et al 2008) show no change owing to mating in the ability of females to clear non-pathogenic bacteria, while Fedorka et al (2007) demonstrated that females infected with a pathogenic bacterium suffer higher mortality if they have mated.…”
Section: Results and Discussion (A) Mating Reduces Female Immune Defementioning
confidence: 99%
“…We also determined whether the change in defence is dependent on the particular combination of male and female genotypes engaging in copulation. We measured genetic variation in both sexes because we were particularly interested in assessing the potential for ongoing sexual conflict in this system, as it has been suggested in the literature that the fitness of males and females may be affected differently depending on the level of immunosuppression females experience after mating, and that this could lead to sexual conflict (Fedorka et al 2007;Lawniczak et al 2007). This hypothesis could be provisionally supported by data we have collected, which suggest that the male ejaculate plays a role in reducing female defence (S. M. Short, M. F. Wolfner & B. P. Lazzaro 2010, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…For the experiments, females were collect as virgins from the culture vials and then were aged for 3 days. This controlled for both age and mating status, which have both been shown to affect immune function (Fedorka et al, 2007;Fedorka and Zuk, 2005;Lawniczak and Begun, 2004;McGraw et al, 2004;Zerofsky et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…18, or, more intriguingly, a mating-induced shift in the focus of the immune response from whole-body to the RT, as has also been suggested in ref. 19.…”
Section: Mating Induces Up-regulation Of Immune-related Transcripts Imentioning
confidence: 99%